La noción de ser humano como primitiva en la filosofía de la psicología de Wittgenstein - Arnao Bergero, Magdalena (Revista de Filosofía, 2008)
The Human being notion has not occupied a privileged place in Wittgenstein specialized literature; however, it is central for the discussion about the attribution of subjective states (the other minds problem) that discuss dualism and conductism, and it is still present in actual discussion about mental state. In this paper I will inquire about this notion and show its primitiveness in Wittgenstein philosophy of psychology.